Revitalisasi Teori Maslahat Mulghâh al-Thûfî dan Relevansinya dalam Pembentukan Perundang- Undangan di Indonesia - Hamzah K (Universitas Islam Negeri Jakarta, 2015)
To make Islam as a guide in life, need to be developed in the form of legislation to have the force of law is clear in its implementation, both personally and nation. The establishment of law in Indonesia need the proper method to be practiced and bring peace, tranquility and mercy for all citizens. Many new problems that arise and can not set legal textually through the Quran and the Sunah. One method that could otherwise be used in the determination of the law is mashlahat mulghâh theory. Prospects for the establishment of Islamic law in the form of legislation is very open because the state guarantees the freedom of each citizen to profess his own religion and to worship according to their religion or belief DOI: 10.15408/ajis.v15i1.2845